Ivermectin in combination with doxycycline for treating COVID-19 symptoms: a randomized trial - Mahmud, Reaz; Rahman, Md. Mujibur; Alam, Iftikher; Ahmed, Kazi Gias Uddin; Kabir, A.K.M. Humayon; Sayeed, S.K. Jakaria Been; Rassel, Mohammad Aftab; Monayem, Farhana Binte; Islam, Md Shahidul; Islam, Mohammad Monirul; Barshan, Anindita Das; Hoque, Mohammad Mahfuzul; et al. (Journal of international medical research, 2021)
Objective We evaluated whether ivermectin combined with doxycycline reduced the clinical recovery time in adults with COVID-19 infection. Methods This was a randomized, blinded, placebo-controlled trial in patients with mild-to-moderate COVID-19 symptoms randomly assigned to treatment (n = 200) and placebo (n = 200) groups. The primary outcome was duration from treatment to clinical recovery. Secondary outcomes were disease progression and persistent COVID-19 positivity by RT-PCR. Results Among 556 screened patients, 400 were enrolled and 363 completed follow-up. The mean patient age was 40 years, and 59% were men. The median recovery time was 7 (4–10, treatment group) and 9 (5–12, placebo group) days (hazard ratio, 0.73; 95% confidence interval, 0.60–0.90). The number of patients with a ≤7-day recovery was 61% (treatment group) and 44% (placebo groups) (hazard ratio, 0.06; 95% confidence interval, 0.04–0.09). The proportion of patients who remained RT-PCR positive on day 14 and whose disease did not progress was significantly lower in the treatment group than in the placebo group. Conclusions Patients with mild-to-moderate COVID-19 infection treated with ivermectin plus doxycycline recovered earlier, were less likely to progress to more serious disease, and were more likely to be COVID-19 negative by RT-PCR on day 14. Trial Registration ClinicalTrials.gov Identifier: NCT04523831. Data Repository ID Dryad. doi:10.5061/dryad.qjq2bvqf6